Fatty acids intake among diverse ethnic groups in Indonesia (Medical Journal of Indonesia, 2005)
The use of dietary pattern specifically fatty acids intake should prove to be an informative and powerful means to augment our understanding of the role of diet in chronic disease particularly CHD. Cross sectional study was implemented to describe the nutrients intake specifically fatty acids intake of 4 (four) ethnic groups in Indonesia, such as Minangkabau, Sundanese, Javanese and Buginese. The percentage of saturated fatty acid (SAFA) to total energy intakes were around 20%. The percentage of polyunsaturated fatty acid (PUFA) to the total energy were about 4.4% to 4.6% among the Sundanese and the Javanese.While among the other two ethnic groups, the percentage of PUFA to total energy were less, 2.6 % among the Minangkabau and 2.8% among the Buginese ethnic. The percentage of mono unsaturated fatty acid (MUFA) to total energy intake were higher among the two ethnic groups, Sundanese and Javanese (6.1% vs. 5.5%). While the percentages of MUFA between the other two ethnic groups Minangkabau and Buginese ethnic were lower (2.6% vs. 2.8%). Based on the ratio of PUFA: MUFA: SAFA, we could consider that Minangkabau and Buginese ethnic groups both had poor quality of dietary fat pattern. Having the poor quality of dietary fat pattern and higher fat intake, we might take into consideration that the Minangkabau ethnic groups, had higher risk toward dyslipidemia compared to the other three ethnic groups. (Med J Indones 2005; 14:242-8)